DEVELOPING ANDROID READER-RESPONSE-STRATEGY-BASED READING MATERIAL IN RELATION TO CHARACTER BUILDING - Okky Leo Agusta; Rita Inderawati; Mgrt.Dinar Sitinjak (Universitas Negeri Islam Sumatera Utara, 2024)
The aim of this study was to develop a set of Android Reader-Response-Strategy-based reading material in relation to character building, it reflected five main character values proposed by National Education Ministry. This study was conducted based on ADDIE (Analysis, Design, Development, Implementation and Evaluation) development research design. The formative evaluation consisted one to one evaluation, small group evaluation, and field trial. There were three students involved in one to one evaluation, nine students in small group evaluation and a real class in a field trial. The validity was reviewed by expert of content, expert of instructional design and expert of Android application design. The mean validity score of the developed product was 3.37 which was categorized as very highly valid level. The practicality was conducted in one to one evaluation and small group evaluation. The practicality of one to one was 3.31 which was at very highly practical level and the practicality in small group evaluation was 3.28 which was at very highly practical level. The reading test material was categorized as effective. It showed that there were 26 students (89.65%) out of 29 students in reading test exceeded MMC (minimum mastery criterion) which was 70.